Adsorptive removal of Congo Red dye from its aqueous solutions by tetraethylenepentamine modified peanut husks composite beads - Kah-Tong Chan; Siew-Teng Ong; Sie-Tiong Ha (Desalination and Water Treatment)
The ability of tetraethylenepentamine modified peanut husks (TEPA-PH) composite beads in the removal of an anionic azo dye, Congo Red (CR) was studied. In batch adsorption studies, various parameters such as contact time, initial dye concentration, pH, dosage and agitation rate were included to study their influence towards the adsorption process. The TEPA-PH composite beads formed were thoroughly characterized by using several techniques which includes Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy, Scanning Electron Microscopy (SEM) and Atomic Force Microscopy (AFM). The experimental data followed the pseudo-second-order kinetic model with R2 close to unity. Among the isotherm models, the experimental data is best fitted to Freundlich isotherm model by having R2 of 0.9948. The maximum adsorption capacity was determined to be 19.5695 mg/g using the Langmuir model. The significant factors were selected using the Plackett-Burman (PB) design and the optimization of the adsorption model was done using the Response Surface Methodology (RSM). With optimum conditions of 180 min of contact time, 62.5 mg/L of initial dye concentration and 0.35 g of dosage, the percentage uptake of CR can reach 77.11%.